The Effect of Nurse Staffing Ratios on Status of Patient Outcome in Emergency Unit at Dr. Lorenzo P. Ziga Memorial District Hospital - Branuelo, Jolly; Alcala, Emerlinda (International Journal of Sustainability and Advanced Integrated Research, 2026)
Nurse staffing shortages in Philippine emergency rooms, particularly at ratios exceeding 1:30, compromise patient outcomes through increased burnout, medical errors, and dissatisfaction, as evidenced by global and local studies highlighting the need for optimal staffing to enhance care quality. This descriptive correlational study examined nurse-to-patient ratios in the Emergency Room of Dr. Lorenzo P. Ziga Memorial District Hospital, Tabaco City, Albay, and their relationship to patient outcomes including mortality rates, complications, satisfaction scores, and length of stay, surveying 50 emergency room nurses and 100 patients using validated questionnaires and hospital records analyzed through Pearson's r and chi-square tests (p
Keywords: Nurse staffing ratios; Patient outcomes; Emergency room; Nurse burnout; T; Philippines